2022
DOI: 10.5194/tc-16-3775-2022
|View full text |Cite
|
Sign up to set email alerts
|

An 11-year record of wintertime snow-surface energy balance and sublimation at 4863 m a.s.l. on the Chhota Shigri Glacier moraine (western Himalaya, India)

Abstract: Abstract. Analysis of surface energy balance (SEB) at the glacier/snow surface is the most comprehensive way to explain the atmosphere–glacier/snow interactions, but that requires extensive data. In this study, we have analysed an 11-year (2009–2020) record of the meteorological dataset from an automatic weather station installed at 4863 ma.s.l. (above sea level) on a lateral moraine of the Chhota Shigri Glacier, western Himalaya. The study was carried out over the winter months (December to April) to understa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 94 publications
4
21
1
Order By: Relevance
“…Consequently, the saturation vapour pressure at the surface is lower, reducing the near-surface vapour pressure gradient and, hence, the sublimation rate. These findings are supported by findings of Mandal et al (2022). Their meteorological data and model simulation also reveal that sublimation rates are reduced during cold surface conditions.…”
Section: Future Research and Recommendationssupporting
confidence: 76%
See 3 more Smart Citations
“…Consequently, the saturation vapour pressure at the surface is lower, reducing the near-surface vapour pressure gradient and, hence, the sublimation rate. These findings are supported by findings of Mandal et al (2022). Their meteorological data and model simulation also reveal that sublimation rates are reduced during cold surface conditions.…”
Section: Future Research and Recommendationssupporting
confidence: 76%
“…In Chapter 3, I showed that sublimation is an important component of the high-altitude water balance. This is supported by findings of Mandal et al (2022). They showed that 16-42% of the seasonal snowfall is returned to the atmosphere due to sublimation using the bulkaerodynamic method driven by in situ meteorological data at a point location (4863 m a.s.l.)…”
Section: Future Research and Recommendationssupporting
confidence: 65%
See 2 more Smart Citations
“…It is important to acknowledge that for higher-altitude glaciers in tropical regions, sublimation is a critical means of ablation 5,[48][49][50] , and this should not be expected to scale with 𝑇𝑒 in the same way that moist enthalpy exchange does. Instead, sublimation results from the flux of latent heat, and so is dependent on the gradient in specific humidity (SI Section 1).…”
Section: Discussionmentioning
confidence: 99%